SERIAL VISION PADA KORIDOR JALAN MENARA KOTA KUDUS - Jamaluddin, Rizqi; Sardjono, Agung Budi; Murtini, Titien Woro (Prodi Arsitektur UNIVERSITAS KEBANGSAAN, 2019)
Abstract: In structuring a city there is a high complexity experienced by cities so that existing problems will not be endless. When conducting city structuring there are many factors that influence in creating a good city environment. In providing a strong identity, there needs to be a harmonious relationship between one place and another. To find out the description of the strong characteristics and the clear need for serial vision scanning. Kudus itself is a city that has interesting characteristics on the road corridor. The corridors in the holy area have unique visual characteristics, which triggers the community to remember a building in that location. In this case, the corridor in the Menara Kudus Mosque Area is interesting to be appointed as an effort to revive the identity of the old city of the holy region through serial vision and its components. This research is considered important enough to be one of the basic studies in its design. In addition, it is very important to maintain the visual character of a corridor.Keyword: Serial Vision, Corridor, Jl.Menara KudusAbstrak: Dalam penataan sebuah kota terdapat kompleksitas yang tinggi dialami oleh kota sehingga permasalahan yang ada tidak akan ada habisnya. Saat melakukan penataan kota terdapat banyak faktor yang mempengaruhi dalam menciptakan lingkungan kota yang baik. Dalam memberikan identitas yang kuat perlu adanya keselarasan hubungan antar satu tempat dengan tempat yang lain. Untuk mengetahui gambaran tentang cirikhas yang kuat dan jelas perlu adanya pemindaian secara serial vision. Kudus sendiri merupakan kota yang memiliki cirikhas yang menarik pada koridor jalan. Adapun koridor yang ada di kawasan kudus mempunyai karakteristik visual unik sehingga memicu masyarakat untuk mengingat sebuah bangunan di lokasi tersebut. Dalam hal ini koridor di Kawasan Masjid Menara Kudus menarik untuk diangkat sebagai upaya mengangkat kembali identitas kawasan kota lama kudus melalui serial vision dan komponen didalamnya. Penelitian ini dirasa cukup penting untuk menjadi salah satu dasar kajian dalam perancangannya. Selain itu sangat penting untuk menjaga karakter visual sebuah koridor.Kata Kunci: Serial Vision, Koridor, Jl. Menara Kudus